2021
DOI: 10.1051/0004-6361/202039781
|View full text |Cite
|
Sign up to set email alerts
|

Properties of gas phases around cosmic filaments atz= 0 in the IllustrisTNG simulation

Abstract: We present the study of gas phases around cosmic-web filaments detected in the TNG300-1 hydro-dynamical simulation at redshift z = 0. We separate the gas into five different phases according to temperature and density. We show that filaments are essentially dominated by gas in the warm-hot intergalactic medium (WHIM), which accounts for more than 80% of the baryon budget at r ∼ 1 Mpc. Apart from WHIM gas, cores of filaments (r ≤ 1 Mpc) also host large contributions from other hotter and denser gas phases, whos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 99 publications
(231 reference statements)
7
34
0
Order By: Relevance
“…As we can see, the number of cosmic filaments that are connected to clusters and the departure from spherical symmetry are significantly correlated for both the DM and the WHIM gasphase. In agreement with Galárraga-Espinosa et al (2021a) who found that WHIM gas phase is strongly dominant in cosmic filaments, we conclude that azimuthal distribution of WHIM tends to follow DM by tracing cosmic filamentary structures connected to clusters at their peripheries.…”
Section: Mass and Connectivity Dependencysupporting
confidence: 92%
See 3 more Smart Citations
“…As we can see, the number of cosmic filaments that are connected to clusters and the departure from spherical symmetry are significantly correlated for both the DM and the WHIM gasphase. In agreement with Galárraga-Espinosa et al (2021a) who found that WHIM gas phase is strongly dominant in cosmic filaments, we conclude that azimuthal distribution of WHIM tends to follow DM by tracing cosmic filamentary structures connected to clusters at their peripheries.…”
Section: Mass and Connectivity Dependencysupporting
confidence: 92%
“…At larger distances from cluster center (> 3R 200 ), the distribution of the gas in temperature-density diagrams appears distributed in the different phases: cold diffuse (IGM), cold dense (halo gas), warm diffuse (WHIM), warm dense (WCGM) and hot gas. This temperature-density distribution is quite similar to the expected distribution of overall cosmic gas in the universe at z = 0 (see figure 2 of Galárraga-Espinosa et al 2021a, which considered all gas cells in the simulation box). Therefore, it suggests that beyond radial distances larger that 3R 200 the influence of cluster environments is no more significant.…”
Section: The Gas Phasessupporting
confidence: 75%
See 2 more Smart Citations
“…Malavasi et al 2021;Kotecha et al 2021, however see also Liao & Gao 2019;Song et al 2021), and the intergalactic medium (e.g. Klar & Mücket 2012;Galárraga-Espinosa et al 2021).…”
Section: Discussionmentioning
confidence: 99%